The mathematical model for decay curve of the nuclei-delayed neutron precursors in experiment at a pulsed electron linear accelerator - Buki, A.Yu.; Gokov, S.P.; Demeshko, O.A.; Kasilov, V.I.; Kokhnyuk, K.S.; Kochetov, S.S.; Mel’nitsky, I.V.; Semisalov, I.L.; Khomich, A.A.; Shopen, O.A. (Вопросы атомной науки и техники, 2009)
On the basis of the notion about six groups of nuclei as delayed neutron precursors, radioactive decay laws and the pulsed mode of accelerator operation, a relationship has been derived to describe the decay curve of nuclei-delayed neutron precursors as a function of the pulse rate of the accelerator, the exposure time, the observation time, the time measurement interval and the number of measurement runs. A pilot experiment on thermal-neutron fission of 235U has been conducted. The aim of the experiment was to check the hardware and the information readout computer program. Based on the expressions derived, an analysis was performed and relative yields of delayed neutrons were determined. The present results are compared to the data obtained by other authors. For further development of the analysis, a question is brought up about the influence of additional conditions on the determination of relative delayedneutron yields. These additional conditions can be represented by certain expressions laid down when measuring delayed neutron yields directly between the accelerator pulses.